Conhecimento docente em ação e o uso de tecnologias digitais no ensino da matemática nos anos iniciais - CONCEIÇÃO, Elenice Rosário da (Universidade Federal do Pará, 2022)
This dissertation is guided by the qualitative approach, based on Action Research according to Thiollent (2008). It is linked to the line of research on Teacher Education for the teaching of science and mathematics in the Graduate Program in Teaching in Science and Mathematics Education. Among other objectives, it aims to verify knowledge in action of teachers who teach mathematics in the early years through TDIC. I highlight a teacher as a research subject who taught the fourth year of basic education, taking the mathematics classes of the early years as the object of observation. The research took place in the midst of teacher training with the use of digital technology for teaching. The questionnaire and audio recordings of tasks were used as data collection instruments, which were later transcribed. As material for analysis, I highlight the information from the questionnaire and the data treated from two tasks planned and developed with three classes of the fourth year of Elementary School, in a public school in Belém do Pará, with TPACK guidelines as the first theoretical contribution. (Knowledge of Content, Pedagogical and Technological). The results obtained demonstrate the relevance of discussing and thinking about the use of Digital Information and Communication Technologies, in view of the technology, pedagogy and content triad, especially regarding Google tools, mobilizing and explaining knowledge to enrich the pedagogical practice and, consequently, the teaching process. teachinglearning. With the completion of the task, it was noticed that some difficulties were overcome by the teacher in view of the use of technological tools. In view of the above, I propose the E-book "TDIC + Mathematics = Teacher knowledge in action" and the website "Integration of technology in teacher training and practice - INTEFORMED" as an Educational Product to enable teachers to access a process of experiences and tools for teaching with Technologies. Therefore, the research presents itself as relevant, considering the social moment experienced by the covid-19 pandemic, in which the need to use digital technologies became more evident, especially in the educational sphere, as well as the use of possibilities aimed at teaching as enriching the school curriculum and the teaching-learning process, especially in mathematics.